Current Stimuli-Responsive Mesoporous Silica Nanoparticles for Cancer Therapy - Thashini Moodley; Moganavelli Singh (MDPI AG, 2021)
With increasing incidence and mortality rates, cancer remains one of the most devastating global non-communicable diseases. Restricted dosages and decreased bioavailability, often results in lower therapeutic outcomes, triggering the development of resistance to conventionally used drug/gene therapeutics. The development of novel therapeutic strategies using multimodal nanotechnology to enhance specificity, increase bioavailability and biostability of therapeutics with favorable outcomes is critical. Gated vectors that respond to endogenous or exogenous stimuli, and promote targeted tumor delivery without prematurely cargo loss are ideal. Mesoporous silica nanoparticles (MSNs) are effective delivery systems for a variety of therapeutic agents in cancer therapy. MSNs possess a rigid framework and large surface area that can incorporate supramolecular constructs and varying metal species that allow for stimuli-responsive controlled release functions. Its high interior loading capacity can incorporate combination drug/gene therapeutic agents, conferring increased bioavailability and biostability of the therapeutic cargo. Significant advances in the engineering of MSNs structural and physiochemical characteristics have since seen the development of nanodevices with promising in vivo potential. In this review, current trends of multimodal MSNs being developed and their use in stimuli-responsive passive and active targeting in cancer therapy will be discussed, focusing on light, redox, pH, and temperature stimuli.